The mucin phenotype does not affect the endoscopic resection outcome of non-ampullary duodenal epithelial tumors - Toya, Yosuke; Endo, Masaki; Yamada, Shun; Oizumi, Tomofumi; Morishita, Toshifumi; Akasaka, Risaburo; Yanai, Shunichi; Nakamura, Shotaro; Eizuka, Makoto; Uesugi, Noriyuki; Sugai, Tamotsu; Matsumoto, Takayuki (Endoscopy International Open, 2021)
Background and study aims Some studies have reported an association between clinicopathological features and mucin phenotypes of non-ampullary duodenal epithelial tumors (NADETs). However, the association between clinical outcomes of endoscopic resection (ER) and mucin phenotypes has not been elucidated. The aim of this retrospective study was to analyze clinical outcomes of ER of NADETs with reference to mucin phenotypes.Patients and methods We retrospectively evaluated the clinical outcomes of ER for NADETs performed from 2006 to 2019 and compared clinicopathological characteristics, ER procedures, and outcomes, including adverse events (AEs) among tumors classified by mucin phenotype. Mucin phenotypes were classified as gastric, gastrointestinal, and intestinal based on immunohistochemical examination. Grade of dysplasia was determined according to the Vienna classification (VCL).Results The proportion of VCL 4/5 was higher in the gastric type (50 %) compared with that in the gastrointestinal (39.1 %, P = 0.009) and intestinal types (5.4 %, P = 0.008), respectively. With no statistical difference in tumor size and ER method among the three groups, no significant difference was observed for ER outcomes, i. e., en bloc and R0 resection rates. In the gastrointestinal and intestinal types, AEs occurred in four cases treated with ESD, but none developed in the gastric type.Conclusions This study suggests that the mucin phenotype does not affect resection outcome. However, considering high malignant potential and tendency for low AE rates, the gastric type NADETs may be more appropriate for proactive ER than the others.